RANCANG BANGUN MESIN PRESS SANDAL WITH MINI CONVEYOR - Sholihuddin, Achmad Nizar; Kariyono, Joko; Perwira, Mada (Program Kreativitas Mahasiswa - Teknologi, 2013)
In a small industrial slippers, sandals profile pengeplongan process is a process that takes a relatively long time (manual system). This resulted in most of the demand could not be met. In addition to the fuel efficiency is still low, it is because the material cutting process occurs according to the length of the rest of the sandals so much material is wasted. Planning press machine should be able to cut the sponge slippers used as an ingredient for the manufacture of slippers. The calculation starts from data collection materials, then searched the force required in order to direncanankan diameter cylinders are used, and the selection of pneumatic components. Furthermore done circuit design and assembly. Final level of testing tools for success. From the calculation, the force required for 5243.3 N with operating pressure 0.7 N/mm2 and 100 mm diameter pneumatic cylinders.